FNB : developing a culture of innovation - Gaylard, Alison (SAGE knowledge. Cases., 2016)
First National Bank (FNB) has become known in the industry as a leader in banking innovation. When CEO Michael Jordaan took over the reins in 2004, he took innovation to a new level through the Innovators campaign. But now, in 2010, he was wondering how to sustain the energy the campaign had engendered in his staff. What more could he do to nurture the spirit of innovation that permeated the organisation?